Metal complexes of crosslinked chitosans. part II. an investigation of their hydrolysis to chitooligosaccharides using chitosanase - Trimukhe, K. D.; Bachate, S.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2007)
This paper investigates the behavior of crosslinked chitosans and metal-complexed crosslinked chitosans under similar hydrolytic conditions. Crosslinked chitosans with trimellitic anhydride, diisocyanatohexane, and dibromodecane as crosslinking agents under heterogenous reaction conditions were used as metal complexing agents by equilibrating them with metal salts such as ZnCl2, MnSO4, CuSO4, CdSO4, Pb(NO3)(2), and HgCl2. Crosslinked chitosan without metal complexation had the same hydrolytic behavior as uncrosslinked chitosan. However, when the crosslinked chitosans were complexed with metals, their rates of hydrolysis and extent of hydrolysis were significantly reduced. Thus, while for chitosan about 840 mu g/ml reducing sugar was produced in 4 h time, and 780 mu g/ml was produced for diisocyanatohexane crosslinked chitosan, only 400 mu g/ml and 320 [mu g/ml reducing sugars were produced for cadmium sulfate with crosslinked chitosan and diisocyanatohexane crosslinked chitosan, respectively. Similar results are obtained for other crosslinking agents. Studies on preincubation of the metal with the enzyme show that of the metals studied, Mn has no effect on preincubatioin with the enzyme, Hg, Cd, Pb, and Cu completely deactivates the enzyme, while Zn reduces the enzyme activity by about 43.3%. Preincubation of the metal salts with the chitosan shows that Hg and Cu completely deactivate the molecule from enzyme hydrolysis, Cd and Zn inactivate it to the extent of 56.8% and 43.3%, respectively, while Mn has no effect. Availability of the amino functions seems to be a key feature for the chitosanase to hydrolyze the chitosan polymer. This was also proved by the significant increase in the extent of hydrolysis for chitosan samples with 88% (final value 1120 mu g/ml reducing sugar) and 85% deacetylation (final value 840 mu g/ml reducing sugar). HPIC studies of the products show that a variety of oligomers are produced in the chitosanase enzyme hydrolytic reaction. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: chitooligosaccharides; Chitosan; chitosanase hydrolysis; Crosslinked chitosan; metal-complexed crosslinked chitosan